THE INFLUENCE OF BANANA BLOSSOM CONSUMPTION ON INCREASING BREAST MILK PRODUCTION IN POSTPARTUM MOTHERS - Ismawati, Iis; Lufar, Nay; Rahma, Naya Aqnia (Siklus : Journal Research Midwifery Politeknik Tegal, 2025)
This study examines the influence of banana blossom (Musa spp.) consumption on breast milk production in postpartum mothers. Banana blossoms are known to be rich in bioactive compounds such as flavonoids, saponins, and tannins, which play a role in influencing lactation hormones, particularly prolactin, and have the potential to increase breast milk production. Using a pre-test and post-test experimental design, breast milk volume was measured before and after a dietary intervention in ten postpartum mothers. The study results showed a significant increase in breast milk production following banana blossom consumption, with the average volume rising from 466.30 ml (SD = 183.30) to 2406.20 ml (SD = 373.43), p 0.001. These findings support previous studies (Buntuchai et al., 2017; Yimyam Pattamapornpong, 2022) demonstrating the effectiveness of banana blossom as a natural galactagogue and highlight its potential as an affordable dietary intervention to enhance lactation outcomes. This research provides additional insights into the role of galactagogues in postpartum care, offering a practical solution to improve breastfeeding success in mothers.